2012 IEEE 23rd International Symposium on Personal, Indoor and Mobile Radio Communications - (PIMRC) 2012
DOI: 10.1109/pimrc.2012.6362511
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient thermal and power aware (ETPA) routing in Body Area Networks

Abstract: Abstract-Research on routing in a network of intelligent, lightweight, micro and nano-technology sensors deployed in or around the body, namely Body Area Network (BAN), has gained great interest in the recent years. In this paper, we present an energy efficient, thermal and power aware routing algorithm for BANs named Energy Efficient Thermal and Power Aware routing (ETPA). ETPA considers a node's temperature, energy level and received power from adjacent nodes in the cost function calculation. An optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 11 publications
0
40
0
3
Order By: Relevance
“…However, such protocols need varied transmissions for updating link-state information that could turn out to be a constraint in implementing macro range of protocols. In [29], the authors Introduced ETPA method which means "Energy Efficient Thermal and Power-Aware routing" that offers solution for proposed factors of relative costing solutions. In addition, certain complex factors like depletion time that could result in lasting communication among the nodes considered in WBASNs.…”
Section: Probabilistic Routingmentioning
confidence: 99%
“…However, such protocols need varied transmissions for updating link-state information that could turn out to be a constraint in implementing macro range of protocols. In [29], the authors Introduced ETPA method which means "Energy Efficient Thermal and Power-Aware routing" that offers solution for proposed factors of relative costing solutions. In addition, certain complex factors like depletion time that could result in lasting communication among the nodes considered in WBASNs.…”
Section: Probabilistic Routingmentioning
confidence: 99%
“…Experimental results have shown that the proposed protocol is able to balance energy consumption within the network and thus guarantees a longer network life time. In addition, the work in [9] considers the node temperature, energy level, and received signal power from adjacent nodes as a cost function while determining the optimal route that minimizes the temperature rise and power consumption of the network. Moreover, the work in [10] adopts node clustering for energy saving since communication among clusters enables shorter transmission ranges.…”
Section: Related Workmentioning
confidence: 99%
“…For NDPs, if there is no entry in the routing table RT (i.e., NULL RT) then the packet is dropped immediately (lines: 2-4). In case of any entries in RT, it searches RT in the same way as in reliability aware algorithm (lines: 5-12) but the DNH is selected based on minimum TR (lines: [13][14][15][16][17][18][19][20] for each node ∈ RT do (6) if PL , < = PL Thre then (7) put node into NH PL (8) end if (9) end for (10) if NH PL = = NULL then (11) Drop the packet immediately (12) else (13) for each node ∈ NH PL do (14) if PR , > = req then (15) put node into NH (16) end if (17) end for (18) end if (19) if NH = = 1 then…”
Section: Temperature Aware Modulementioning
confidence: 99%
“…Inputs: NDPs and RT or RCDPs and NH (1) for each packet " " ∈ NDPs or RCDPs do (2) if ∈ NDPs then (3) if RT = = NULL then (4) drop the packet immediately (5) else (6) for each node ∈ RT do (7) if PL , > = PL Thre then (8) put node into NH PL (9) end if (10) end for (11) if NH PL = = NULL then (12) drop the packet immediately (13) else (14) for each node ∈ NH PL do (15) put TR of into TRL (16) end for (17) DNH = ∈ NH PL whose TR = = min(TRL) (18) send the packet to DNH (19) end if (20) end if (21) else if ∈ RCDPs then (22) for each node ∈ NH do (23) put TR of into TRL (24) end for (25) DNH = ∈ NH whose TR = = min(TRL) (26) send the packet to DNH (27) end if (28) end for Algorithm 2: Temperature Aware Algorithm.…”
Section: Reliability Estimatormentioning
confidence: 99%